Experiences from the past. Comparative research between hospital archive sources and human remains - Ciliberti, Rosagemma (Medicina Historica, 2023)
Criminal anthropology has obtained great interest in the field of History of Medicine. Lombroso had several followers between the late 19th and the first half of the 20th century and the literature of that time showed that the positivistic tools of biomedicine were useful to demonstrate a profound connection between “anomalous behaviors and anomalous anatomy”. Although these concepts are outdated, it is interesting to highlight how scientific methods adopted in this case by De Blasio, or the comparison between the archival sources and bone samples, is extremely modern for the time.